β2microglobulin levels, clinical and sociodemographic variables in patients with recently diagnosed chronic lymphoproliferative syndrome - Pedro Javier Sánchez Sánchez; Julio Dámaso Fernández Águila; Pedro Sánchez Frenes; María de Jesús Sánchez Bouza; Karelys Díaz Alfonso (Medisur)
Background: β2microglobulin is recognized as a tumor marker for different purposes in malignant hematopathies of lymphoid lineage; however, there is no history of its use in the Cienfuegos province. Objective: to describe the sociodemographic and clinical characteristics and the distribution of serum β2microglobulin levels in patients with chronic lymphoproliferative syndrome and their relationship with clinical stages and response to first-line treatment. Methods: cross-sectional descriptive observational study. The series was made up of all adult patients (universe 50) recently diagnosed (without starting specific antitumor therapy) of multiple myeloma, chronic lymphoid leukemia, non-Hodgkin lymphoma and Hodgkin lymphoma, admitted to the Hematology Service of the Dr. Gustavo Aldereguìa Lima General University Hospital, during the year 2020. The information was obtained through documentary review of medical records and laboratory tests. The analyzed variables were: sex, age, skin color, β2microglobulin levels, type of disease, clinical stages and response to treatment. Results: 84% of the series presented high levels of the analyte, more accentuated in myeloma. A relationship was found between the stratified levels of β2microglobulin with the clinical stages and the response to first-line treatment. Conclusions: the sociodemographic characteristics and the clinical variables observed do not differ substantially from what was reported. The distribution of β2microglobulin levels is suggestive of a direct relationship between clinical stages and an inverse relationship with response to treatment.